2002
DOI: 10.1093/jac/dkf806
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of macrolide resistance mechanisms among Streptococcus pneumoniae and Streptococcus pyogenes isolated from the PROTEKT 1999-2000 study

Abstract: In this study, the distribution of macrolide resistance mechanisms was determined for isolates of Streptococcus pneumoniae and Streptococcus pyogenes obtained from the PROTEKT 1999-2000 study (a global, longitudinal study of the antibacterial susceptibility of bacterial pathogens associated with community-acquired lower respiratory tract infections). The global macrolide resistance mechanism distribution results for 1043 macrolide-resistant S. pneumoniae isolates collected from 25 countries were as follows: 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
120
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 35 publications
5
120
0
4
Order By: Relevance
“…As this report shows, the mef(A) gene clearly predominates in the United States; other research has suggested that the same is true in Canada (20). In contrast, for Europe overall, erm(B) prevails among macrolide-resistant S. pneumoniae isolates (although this varies widely from country to country) (13). In the Far East, the prevalence of macrolide resistance mechanisms among isolates of S. pneumoniae is more diverse.…”
Section: Discussionmentioning
confidence: 97%
“…As this report shows, the mef(A) gene clearly predominates in the United States; other research has suggested that the same is true in Canada (20). In contrast, for Europe overall, erm(B) prevails among macrolide-resistant S. pneumoniae isolates (although this varies widely from country to country) (13). In the Far East, the prevalence of macrolide resistance mechanisms among isolates of S. pneumoniae is more diverse.…”
Section: Discussionmentioning
confidence: 97%
“…Regional differences in mechanisms of resistance need to be taken into consideration when deciding whether to report clindamycin susceptibility results on the basis of in vitro test results. Testing by the double-disk diffusion method would be an approach that could be used to address this issue, especially for GAS.In Canada, as in other regions of North America and Europe, the rates of erythromycin resistance among isolates of the group A Streptococcus (GAS; Streptococcus pyogenes) and the group B Streptococcus (GBS; Streptococcus agalactiae) have been increasing (1,8,16). In Ontario, Canada, the rate of erythromycin resistance among GBS isolates has increased from 5 to 13% over a period of 3 years (4).…”
mentioning
confidence: 99%
“…On the other hand, target modification due to methylase, encoded by ermB, confers macrolide-lincosamide-streptogramin B (MLS B ) resistance (10). Among Japanese clinical isolates of S. pneumoniae, 42.7, 52.7, and 3.3% of strains have mefA, ermB, or both genes, respectively (6).…”
mentioning
confidence: 99%